Glucose and melamine derived nitrogen-doped carbonaceous catalyst for nonradical peroxymonosulfate activation. (January 2020) - Zhang, Yu; Pan, Honghui; Murugananthan, Muthu; Sun, Peng; Dionysiou, Dionysios D.; Zhang, Kaikai; Khan, Aimal; Zhang, Yanrong
Abstract: A novel metal-free nitrogen doped carbon material was synthesized by post doping of nitrogen (different amounts of melamine) into carbon substrate derived from glucose, at 550 °C under nitrogen protection. Despite the optimized catalyst has a low nitrogen content of 2.16%, it could effectively activate PMS and exhibited an excellent catalytic performance for phenol degradation with an exceptionally low activation energy. Experiments showed the degradation rates of phenol by the catalyst upon N-doped was 29 times higher than that by carbon substrate, and the reaction pathway of PMS activated transformed from free-radical pathway of carbon substrate to non-radical process. Further, all experimental and theoretical investigations demonstrated the critical role of pyrrolic –N in carbonaceous material to the PMS activation for the first time, which attracts the electrophilic species of PMS and drives the electron transfer towards PMS, thereby the performance of the catalysis was enhanced. The catalytic process performed on various aromatic compounds with different substituents showed a selective degradation dependent on ionization potential (IP). The simple and economical preparation method and the efficiency of the catalyst developed in the study make the activation toward PMS a viable approach for a practical large-scale industrial application. Graphical abstract: Image 1